The influence of prosocial motivation and civility on work engagement:The mediating role of thriving at work - Ghulam Abid; Iqra Sajjad; Natasha Saman Elahi; Saira Farooqi; Asma Nisar (Cogent Business & Management, 2018)
Thriving at work is a psychological state in which employee experience both the sense of vitality and learning. Drawing on Self-Determination Theory, Job Demands and Resources model, and Socially Embedded Model of thriving, our study examines the direct influence of two behavioral antecedents (i.e. prosocial motivation and civility) on work engagement. Moreover, we also investigated the mediating mechanism of thriving at work in the relationship between workplace behavioral antecedents and work engagement. Data were collected in two-wave time lagged cross-sectional time horizon with a gap of two weeks from diverse sample. Using PROCESS macro by Hayes on actual sample of 239 employees from various job functions, strong empirical support is found for all the direct and indirect hypothesized relationships. The finding of the study contributes to the better understanding of the most emerging construct, namely, thriving at work. Theoretical and practical implications along with recommendations for further empirical research on thriving at work are also provided.
Keywords: 650